UNCOVERING LEGAL GAPS IN DIGITAL BANKING: CUSTOMER PROTECTION AND BANK ACCOUNTABILITY IN INDONESIA - Sriono; Risdalina; Kusno; Kumalasari M, Indra; Syahyunan, Hengki (Faculty of Law, Universitas Pasundan, 2024)
The rapid growth of digital banking in Indonesia has necessitated robust legal frameworks to protect digital bank users. This study examines the legal protection available to digital bank customers, focusing on the confidentiality of personal data and the responsibilities of banks under Indonesian law. Utilizing a normative juridical research method, the study relies on library research and an analysis of relevant laws and regulations. The findings reveal that the current legal framework for safeguarding the confidentiality of bank customer data in Indonesia is fragmented and lacks a unified regulatory approach. Legal protection remains incomplete, as it relies on the interplay of multiple regulations without offering comprehensive safeguards. Moreover, the existing mechanisms for addressing breaches of data confidentiality place responsibility primarily on banks, with criminal and administrative liabilities serving as the main avenues for recourse. The novelty of this research lies in its critical evaluation of the gaps in Indonesia's regulatory landscape concerning digital banking, highlighting the need for a cohesive legal framework to ensure stronger protections for customer data. This study contributes to the discourse on digital banking regulation by providing a nuanced understanding of the challenges in safeguarding customer data in Indonesia. It offers valuable insights for policymakers, legal practitioners, and financial institutions in enhancing data protection measures and fostering trust in digital banking.